The effect of compressive trabecular bone-cephalocervical implant relationship on stability in intertrochanteric femoral fractures: a clinical review and biomechanical research - Fei, Lincong; Liu, Jinhui; Zhao, Liang; Mou, Can; Fang, Wei; Ye, Junwu (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionCompressive trabecular bone plays a vital role in load transmission within the proximal femur, and regional variations in cancellous bone distribution have been shown to affect implant stability. However, the biomechanical influence of the spatial relationship between compressive trabecular bone and cephalocervical implants on postoperative fracture stability in intertrochanteric femoral fractures remains unclear.MethodsIn this study, we conducted a retrospective analysis of 64 patients treated with proximal femoral nail antirotation (PFNA) Lever arm parameters reflecting the spatial relationship between compressive trabecular bone and the cephalocervical implant were measured on initial postoperative anteroposterior and lateral radiographs, while the zonal classification of the implant relative to the trabecular architecture was assessed to evaluate its impact on early femoral head varus and helical blade displacement. Additionally, seven finite element models with different implant positions were established to investigate the biomechanical mechanisms underlying stability.ResultsThe results indicated that, a larger trabecular bone-implant lever arm and lower bone mineral density (BMD) independently increased the risks of femoral head varus (p < 0.01) and blade displacement (p < 0.01). Positioning the implant within Zone C of the trabecular architecture was associated with reduced incidences of femoral head varus and implant displacement (p < 0.05). Biomechanical analysis further demonstrated that placing the implant in Zone C with minimized lever arm resulted in the smallest femoral head varus, blade displacement, and the least apparent stress concentration at the implant tip within cancellous bone.DiscussionThese findings suggest that intraoperative placement of cephalocervical implants should aim to reduce the trabecular bone-implant lever arm and prioritize positioning within Zone C of the trabecular architecture to enhance early stability. However, further validation through comprehensive finite element analyses and biomechanical experiments is required.